2018
DOI: 10.1093/mnras/sty902
|View full text |Cite
|
Sign up to set email alerts
|

Star formation history of the Galactic bulge from deep HST imaging of low reddening windows

Abstract: Despite the huge amount of photometric and spectroscopic efforts targetting the Galactic bulge over the past few years, its age distribution remains controversial owing to both the complexity of determining the age of individual stars and the difficult observing conditions. Taking advantage of the recent release of very deep, propermotion-cleaned colour-magnitude diagrams (CMDs) of four low reddening windows obtained with the Hubble Space Telescope (HST), we used the CMD-fitting technique to calculate the star… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
79
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 72 publications
(94 citation statements)
references
References 51 publications
(58 reference statements)
15
79
0
Order By: Relevance
“…When taking into account distance, reddening, and metallicity effects, Haywood et al (2016) showed that the MS-TO color spread of a purely old stellar population would be wider than what is observed, and thus advocating for the presence in the bulge of a conspicuous population of young and intermediate-age stars. Very similar results are presented by Bernard et al (2018) who calculated the star formation history of four bulge fields, including that of Clarkson et al (2011). Their findings suggest that over 80% of the stars are older than 8 Gyr, but also suggest the presence of star formation as recent as ∼1 Gyr.…”
Section: Introductionsupporting
confidence: 77%
See 2 more Smart Citations
“…When taking into account distance, reddening, and metallicity effects, Haywood et al (2016) showed that the MS-TO color spread of a purely old stellar population would be wider than what is observed, and thus advocating for the presence in the bulge of a conspicuous population of young and intermediate-age stars. Very similar results are presented by Bernard et al (2018) who calculated the star formation history of four bulge fields, including that of Clarkson et al (2011). Their findings suggest that over 80% of the stars are older than 8 Gyr, but also suggest the presence of star formation as recent as ∼1 Gyr.…”
Section: Introductionsupporting
confidence: 77%
“…Therefore, prior to any attempt to age-dating the bulge population from its observed CMD, special care must be taken to remove the contribution of the intervening disk population along the line of sight. This can be done either by using proper motions (see Clarkson et al 2008Clarkson et al , 2011Kuijken & Rich 2002;Bernard et al 2018) or statistically with a disk controlfield (e.g., Zoccali et al 2003;Valenti et al 2013). Both methods require some assumptions, and therefore have their own pros and cons.…”
Section: Disk Decontamination Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…No a-priori constraint on the age-metallicity relation is adopted: TheStorm code solves simultaneously for age and metallicity within the range covered by the simple stellar populations. For more details on the fitting procedure and error calculation, the reader is referred to published references 52,63,68 .…”
Section: Methods 1 Data Selectionmentioning
confidence: 99%
“…On the other hand, although the majority of MWB stars are known to be old (∼10 Gyr), it remains to be understood if there is a significant fraction of young stars (<5 Gyr), specifically at the metal-rich end (see Renzini et al 2018, and references therein). However, the MWB age-metallicity relation recently found by Bernard et al (2018), that favours a wide range of ages for metalrich stars, can be used to show that in this case (for the well known spatial variations in mean metallicity) the mean age of the MWB could spatially vary from 10 Gyr in the outer regions to up to 6 Gyr closer to the plane. Even when these maximum population gradients are considered, the theoretical mean magnitude variation of the RC would be of < 0.10 magnitudes (see Fig.…”
Section: Introductionmentioning
confidence: 93%